Development of eddy current testing instrument on metal testing for non-destructive testing applications - Elva Alias (2019)
Eddy current facilities are rapidly developing in the field of industry and the effectiveness of the eddy current testing (ECT) instrument is well established on market and yet, the instruments were very expensive and hard to get in this country. Moreover, the optimization for the specification of metals testing is still lacking in research and development. The alternative approach as discussed in this research is by design and construct a low-cost non-destructive metal testing instrument using eddy current method that able to examine the signal imperfection, detect thickness (1.5, 3.0 and 5.0 mm) and lift-off distance (1.0-5.0 mm). The frequency ranges between 250 kHz-3.5 MHz by using 50 ohms function generator is selected to find the optimal frequency for each metal testing (i.e., Brass, Cu, Mg Alloy, Ni and Ti). The important part in constructing the ECT instrument is the dual coil sensor which is known as exciter-receiver coil designed in appropriate turns of coils and the instrument amplifier that give a high output voltage that excel at extracting very weak signals from noisy environments. The output voltage signals from the sensor circuit of the ECT instrument were analyzed and compared. The result of this research showed that the designed ECT instrument able to examine the signal imperfection and also to detect the thickness. The lift-off distance for the ECT instrument is at 1 mm. Meanwhile, the optimal frequency on each metal for the ECT instrument is at 2.90 MHz for Brass, 2.95 MHz for Copper, 2.89 MHz for Magnesium Alloy, 2.85 MHz for Nickel and 2.83 MHz for Titanium. The ECT instrument that is developed from this study can efficiently generate an accurate output reading and suitable for industrial application requirements.